Refractive index of solutions at high concentrations - Mat Yunus, Wan Mahmood; Abdul Rahman, Azizan (Optical Society of America, 1988)
The refractive index of liquid solutions at the He–Ne laser wavelength, 0.6328 μm, is presented. The measurements were carried out using the conventional minimum deviation method of an equilateral hollow glass prism. The refractive indices of sucrose, sodium chloride, glucose, and caster sugar solutions for a range density varying from distilled water to a saturated condition were measured. The result shows that at higher of concentrations a slight curvature can be seen from the plot of refractive index vs concentration of solution. However, the refractive index of sucrose shows a linear relationship with concentration. The accuracy of the measurements is estimated to be better than 0.3%.